Influence of development the motor intellect on mental capacity orphaned children 6–7 years old - Косівська, С. В.; Бондаренко, С. В. (Slobozhanskyi Herald of Science and Sport, 2011)
The article examines the influence of development the motor intellect on the values of mental sphere, in particular mental health in general (integral value) and its individual components (volume, intensity and quality). Mental capacity of orphaned children 6–7 years old is considered as an integral value of preparedness for school and a sort of «background» on which there is a realization of all the components of intellectual activity. Tested in the experiment offered means of developing motor intellect (by raising the level of coordination abilities).